Correlates of the use of the case method of teaching - Bermoy, Emiliano Simasio 1947- (Quezon City [s.n.], 1975)
A questionnaire was administered to 76 professors (about 50 percent of the graduate faculty members of some schools) in Metropolitan Manila. Certain student variables such as heterogenous occupational background, emotional maturity, varied educational background and amount of time of preparation for lessons were found to favor the use of the case method of teaching. Certain criteria such as realism, cases designed to meet the training needs of the student, controversiality, significance, the indigenous, multi-sidedness, informativeness were considered important by the professors in judging the appropriateness of a case for instructional purposes. The professors believe that the case method is more effective than other methods of teaching and training administrators and managers for managerial skills.
Thesis (M.Ed.) -- University of the Philippines.
Mimeographed.
Keywords: Case method; Teaching